Avaliação prognóstica dos níveis séricos e teciduais dos biomarcadores MUC-1, MUC-16 e HER-2 em carcinomas mamários caninos: associação com a sobrevida dos pacientes e com a expressão tecidual de RE, RP, KI-67 e E-Caderina - Liliane Cunha Campos (2015)
Advances in molecular biology provides an increasing demand for the identification of tumor biomarkers that aid in early diagnosis, prognosis and more effective mammary cancer treatments . Molecules associated with the presence of cancer have been extensively investigated and used in clinical practice in human medicine, such as serum overexpression demucinas MUC-1 and MUC-16, and overexpression of epidermal growth factor HER-2. Despite the high incidence of mammary tumors in female dogs, few studies address the relationship of serum and tissue expression of MUC-1 and HER-2 in canine mammary carcinomas and to investigate its relationship with the presence of metastases in regional lymph nodes. In addition, to evaluate and correlate serum levels and tissue expression of MUC-1 and MUC-16 dogs with metastatic breast carcinoma with survival and tumor expression of estrogen receptor (ER), progesterone receptor (PR), E-cadherin, HER-2 and ki-67. For the study were selected 38 dogs diagnosed with breast carcinoma and lymph node metastasis who underwent tumor resection followed by chemotherapy., 14 dogs diagnosed with breast carcinoma without evidence of lymph node metastases and 20 otherwise healthy dogs. The immunoassays were conducted to MUC-1, MUC-16 and HER-2 by ELISA according to the protocol established by the manufacturer. Serum levels were measured in surgical time and during the treatment period for metatático group. Immunohistochemistry was performed to MUC-1, MUC-16, ER, PR, E-cadherin, HER-2 and Ki-67. As a result there was a significantly higher concentration of MUC1 serum in dogs with mammary carcinoma with lymph node metastases and a significant decrease in serum expression of MUC-1 and MUC-16 after chemotherapy with increased survival time of the animals . The immunostaining of ER, PR, E-cadherin, HER-2 and Ki-67 was not associated with serum and tissue expression of MUC-1 and MUC-16. The findings suggest that the expression of mucins is independent of the expression of prognostic factors ER, PR, E-cadherin, HER-2 and Ki67 and serum levels of mucin can be used to assess tumor response against the treatment, being MUC-1 is an ancillary diagnostic tool in metastatic mamamary gland carcinomas in the canine species.